The Effectiveness of Dhikr Toward Decreasing Anxiety and Labor Pain During Active Phase of First Stage among Primigravida - Irma Nurbaeti (Jurnal Ners, 2015)
Introduction: Childbirth is an event that causes stress to the mother. Anxiety and pain during labor, if not handled properly will disrupt the process of birth. Interventions to do is dhikr to God. The purpose of this study was to determine the effectiveness of dhikr to reduce anxiety and pain during the active phase of labor.Methods: The study used a quasiexperimental design involving control groups were measured pretest and posttest. The samples were 40 moeslem primigravida with 37–42 weeks gestation and cervical dilation > 3 cm were taken by purposive sampling. Data was collected using a questionnaire (Taylor Manifest Anxiety Scale) and observation of labor pain (Visual Analog Scale) per hour. Multivariate data analysis using ANOVA test at α = 0.05.Results: This study showed that dhikr was effective to reduce the level of anxiety during labor in primigravida (59.8%). The average score of maternal anxiety and pain felt by mothers during childbirth have decreased, with a value of p = 0.001.Conclusion: Primigravida who did dhikr tend to experience mild anxiety during delivery process, while primigravida who did not perform dhikr is likely to experience more severe anxiety. Dhikr is also effective in reducing labor pain during the active phase of labor.